PEMBUATAN DAN UJI ORGANOLEPTIK SEDIAAN LULUR TRADISIONAL KAYA ANTIOKSIDAN DARI DAUN KELOR (Moringa oleifera) DAN TEPUNG BERAS KETAN HITAM (Oryza sativa var glutinosa) DENGAN PENAMBAHAN KULIT JERUK NIPIS (Citrus aurantifolia) - Lestari, Tella; Djamaluddin, Agus; Handayani, Reti Puji (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: Traditional scrubs are cosmetic preparations originating from fresh natural ingredients or dried materials. As the "back to nature" understanding is an increase in the demand for natural ingredients of cosmetics containing high antioxidants, one of which is the kelor leaf with tannin content with the addition of black sticky rice flour and lime skin as an additional material on traditional scrubs. Research Objectives: Make traditional scrub preparations from Moringa leaves and black sticky rice flour with the addition of lime leather, and make a stable preparation through organoleptic testing and knowing the favorite test. Method: Using action research design (Action Research) to identify and find solutions from a problem studied. The research flow starts from planning, action, observation and reflection (repairs). The independent variables of this study are melor leaves and black sticky rice flour with as many as the edge of lime (1.3g: 2g: 6g); (1.3g: 2g: 7g) and (1.3g: 2g: 8g) with different storage temperature observations. The dependent variable is the physical properties of traditional scrubs seen from the color, aroma and texture and the favorite of panelists. Data collection uses the observation method for organoleptic tests carried out by 20 panelists. Results: The results of the study showed organoleptic traditional stable dosage for 3 weeks of storage. And the results of the three formulations of the formulation, obtained by the most preferred F3 in storage at cold temperatures with a composition of the 1.3g Moringa leaf composition, 2G black sticky rice flour & Lime Limit 8G with lime scented criteria, brownish green, the scrub is easily removed when rubbed , re-textured and can lift dirt on the surface of the skin). Conclusion: The results of organoleptic testing and the preference test carried out in the three formulations can be said to be stable.